Mitigating gut dysbiosis induced by biofilm-forming pathogens: therapeutic potential of LAB-derived bacteriocins - Ravi, Abinash; Pan, Ieshita (Frontiers in Microbiology, 2026)
IntroductionThe gut-brain axis plays a critical role in bidirectional communication system connecting intestinal and neurological health. Imbalance in this system, often caused by gut dysbiosis and pathogenic biofilm formation, can result in inflammation, intestinal barrier dysfunction, and microbial imbalance.MethodsLAB isolates were screened for antimicrobial and antibiofilm activity against Escherichia coli and Serratia marcescens. The most effective strain, C82, was identified through morphological, biochemical and 16S rDNA sequencing. Bacteriocin production, and stability were assessed and optimized. The functional efficacy of the bacteriocin was tested in a zebrafish larval gut dysbiosis model.ResultsLactiplantibacillus pentosus C82, confirmed through 16S rDNA sequencing (NCBI GenBank submission ID: SUB14502111, accession number PP860573), demonstrated strong antimicrobial activity, with inhibition zones of 1.2 cm against E. coli and 1.4 cm against S. marcescens. The bacteriocin reduced inflammation and improved gut barrier integrity. It upregulated IL-10, Claudin-5a, ZO-1, Nfe2l2a, and Hmox1a, while downregulating TNF-α, csgD, and bsmA.Discussion and conclusionThese results establish L. pentosus C82 bacteriocin as a safe, stable, and potent natural antimicrobial agent with significant antibiofilm, antioxidative, and gut-protective effects. It shows promise as a bio-therapeutic candidate for restoring microbial balance, addressing gut dysbiosis, and influencing the gut-brain axis. However, the study was limited to short-term evaluation in zebrafish larvae, which may not fully represent the complexity of the mammalian gut. Further research involving long-term exposure and higher animal models is necessary to validate its therapeutic potential.